Toksisitas Campuran Ekstrak Daun Sirsak (Annona muricata L.) dan Daun Alpukat (Persea americana Mill.) terhadap Larva Nyamuk Aedes aegypti L. dan Pemanfaatannya Sebagai Leaflet - Meilinda Nurima Santi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health problem in Indonesia with an increasing incidence, one of which is transmitted by the presence of the Aedes aegypti mosquito as the main vector. Mosquito larvae control generally uses chemical larvicides such as abate, but long-term use has the potential to cause resistance and environmental pollution. Therefore, more environmentally friendly larvicidal alternatives are needed. One of them is through the use of botanical insecticides. This study aims to analyze the toxicity of a mixture of avocado leaf extract (Persea americana Mill.) and soursop leaf extract (Annona muricata L.) with a ratio of 2:1 on the mortality of Aedes aegypti larvae and to analyze the feasibility of the research results as a leaflet medium. This study is a laboratory experimental study with a Completely Randomized Design (CRD) design. The samples used were late third to early fourth instar Aedes aegypti larvae, the Lethal Concentration 50% (LC₅₀) was determined after 48 hours of exposure. Larval mortality data was analyzed to determine the toxicity level of the extract mixture. The results were then used to develop a leaflet and tested for feasibility by a validator. The results showed that the mixture of soursop and avocado leaf extracts had an LC₅₀ value of 560,538 ppm. This value is categorized as toxic because it is below 1000 ppm, making it a potential natural biolarvicide. The leaflet developed based on the research results was considered suitable as an information and educational medium. The conclusion of this study is that the mixture of soursop and avocado leaf extracts is effective as a botanical larvicide and can be used as a leaflet medium to support environmentally friendly dengue control efforts.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Aedes aegypti L.; LC50; Botanical biolarvicide